Pengembangan Lembar Kegiatan Siswa (LKS) Berbasis Potensi Lokal pada Mata Pelajaran Biologi SMA Kelas XII - Lase, Natalia Kristiani; Sipahutar, Herbert; Harahap, Fauziyah (Jurnal Pendidikan Biologi, 2016)
This research was aimed to develop a Student Activity Sheet (SAS) based on local potency for biology grade XII which is feasible empirically. Eligibility Worksheet was obtained through validation of subject matter experts to assess the feasibility of the content and presentation of the feasibility of worksheets, design expert to assess the feasibility of the design worksheets to SAS developed. Exploiting local potency in accordance with a curriculum that gives freedom to each school consider the potency of the school and the surrounding area. This can be done by incorporating elements of local potency in learning activities through the creation of learning media in the form of worksheets. Examples of local potencies have been integrated into the SAS are distilled palm wine processing (integrated into cell metabolism, fermentation alcohol), the activity of the material have been incorporated in a biotechnology are activities of coconut extraction to produce edible oil. This research and development using 4-D model of development research which comprises the step of define, design, develop and disseminate, however the disseminate stage of this study was not done. The procedure starts from the development stages: (1) problem analyze; (2) design of SAS; (3) validation and field trials SAS. The instruments used were sheets covering the aspects of feasibility validation of content, presentation feasibility, feasibility of the design and questionnaire responses of teachers and students. Data validation and the questionnaire responses of teachers and students were analyzed descriptively qualitative. Feasibility content and feasibility contents presentation SAS based on local potency at biology grade XII has been developed by subject matter experts is very good, in which the feasibility of the content had an average percentage score of 88.10% and feasibility aspects of the presentation of SAS has an average percentage score of 91.35 %. Feasibility design SAS based on local potency at biology grade XII has been developed according to the expert design is very good with a percentage score of 97.00%.